Nutritional profile of patients with chagas heart disease admitted to an Intensive Care Unit (Research, Society and Development, 2022)
The objective was to describe the nutritional profile of patients with heart disease of Chagas' disease, admitted to an Intensive Care Unit (ICU). Sociodemographic, biochemical, clinical and anthropometric data were collected at the time of admission. Patients, five men and four women. Majority, over 60 years old; black or brown race/color; coming from the urban area; active profession; incomplete elementary education; income higher than 1 minimum wage; no smoker or drinker; sedentary; with arterial hypertension and congestive heart failure. Arm circumference, most with low reserve and risk for deficit. Body mass, below ideal in males and females. Calf circumference, average below recommended. Body Mass Index, in the majority, classified underweight. Aspartate and alanine aminotransferases, gamma glutamil transferase, urea and creatinine were above the recommended, in male and female gender. Most of those evaluated presented nutritional depletion and alterations in renal and hepatic function at the time of ICU admission.